Pengaruh Penyuluhan Terhadap Peningkatan Pengetahuan Pada Kader Tentang Penyakit Stroke Dalam Upaya Mencegah Dan Menanggulangi Penyakit Stroke - Budi Rianto; Rudi Karmi (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2019)
The incidence of stroke can be fatal if there is no proper treatment but with good knowledge the prevention program and stroke prevention can work well. PKM Leuwigajah cadres’s are community leaders appointed to assist the public health movement. that is expected by the government in preventing and overcoming stroke.. The researcher wanted to know the success of the stroke education given to the Leuwigajah PKM cadres’s to reference the follow-up of the prevention and prevention. This research is a descriptive correlative study with a cross sectional approach. The population are 26 persons. The result of analyzed is that the knowledge enaught (50%), and after training became almost all of them were 93.2% with good knowledge. while bivariate uses independent simple t test non parameteric. With the results of the value of P = 0.000 less than 0.05, it mean that there is an effect of cadre training on stroke disease before being given education. Thus, it is expected that the results of this study can be used as a teaching material in consideration of decision making in the effort to prevent and prevent stroke.